Consumer decision-making styles under different education background (specific in Finance and Engineering) in banking and financial services - Mei, Dan (2017)
Based on the literature review of the research in the consumer decision-making style and the relationship between different education background and consumer decision-making, this dissertation using the factor analysis method. It aims the individuals with finance or engineering background as the research subject, and conduct a survey with consumer decision-making style questionnaire of the banking and financial services. To explore the relationship between consumer decision-making style and different education backgrounds in the field of banking and financial services. This dissertation aims to clarify the internal mechanism of consumer decision-making style under the influence of different education background, and provide some guidance for the marketing of banks and the financial institutions. The result shows: